Sistem Informasi Absensi Karyawan Pada PT Harja Gunatama Lestari Bandung - . Rinawati; Pitri Candrawati (STMIK Mardira Indonesia, Bandung, 2013)
Technology Development from year to year is fast becoming an increasing serious challenge to user of the technology it self and encourages every sector, both formal and informal organinations or other agencies in order to supporting work activities so as to produce the information fast, precise, accurate. PT Harja Gunatama Lestari as a trading company that its main activity is buying and selling of course need good management in managing its employees which will have a positive impact for the development of the company itself, then the required information efficiently in maintaining its existence and know by the public.One of the company’s efforts to support this is to use a good computer system. To get a good system then conducted a study of existing system. The next stage is to conduct analysis to indentify weakness and deficiencies of the system, then tried to design a system that is a Flow Map, Data flow Diagram, Data dictionary, informatianprocessing and final phase of implementation that converts design into programing language. Keywords: system; information; attendance